Cefuroxime axetil loaded solid lipid nanoparticles for enhanced activity against S. aureus biofilm - Singh B.; Vuddanda P.R.; M.R. V.; Kumar V.; Saxena P.S.; Singh S. (My University, 2025)
The present research work is focused on the development of solid lipid nanoparticles of cefuroxime axetil (CA-SLN) for its enhanced inhibitory activity against Staphylococcus aureus produced biofilm. CA-SLN was prepared by solvent emulsification/evaporation method using single lipid (stearic acid (SA)) and binary lipids (SA and tristearin (TS)). Process variables such as volume of dispersion medium, concentration of surfactant, homogenization speed and time were optimized. The prepared SLN were characterized for encapsulation efficiency, drug polymer interaction studies (DSC and FT-IR), shape and surface morphology (SEM and AFM), in vitro drug release, stability studies and in vitro anti biofilm activity against S. aureus biofilm. Among the process variables, increased volume of dispersion medium, homogenization speed and time led to increase in particle size whereas increase in surfactant concentration decreased the particle size. SLN prepared using binary lipids exhibited higher entrapment efficiency than the single lipid. DSC and FT-IR studies showed no incompatible interaction between drug and excipients. CA-SLN showed two folds higher anti-biofilm activity in vitro than pristine CA against S. aureus biofilm. © 2014 Elsevier B.V.